Analisis kemampuan literasi numerasi siswa kelas IV SD dalam menyelesaikan soal matematika - Khusnul Khotimah; Mega Natasya; Yuvita Rahmawati; Ainurisa Prastyo; Rara Wesya Candra Manuwati (Universitas PGRI Madiun, 2026)
Numeracy literacy is one of the essential competencies that elementary school students need to develop critical thinking and problem-solving skills in mathematics learning. However, various assessment results indicate that Indonesian students' numeracy literacy skills still need improvement. This study aims to analyze the numeracy literacy skills of fourth-grade elementary school students in solving mathematics problems through a Systematic Literature Review (SLR). Articles were identified using the Publish or Perish application through the Google Scholar and Semantic Scholar databases, covering publications from 2020 to 2026. Based on the established inclusion and exclusion criteria, ten relevant articles were selected and analyzed using content analysis. The findings reveal that the numeracy literacy skills of fourth-grade students are generally at a low to moderate level. Most students experience difficulties in understanding problem contexts, identifying relevant information, selecting appropriate solution strategies, and interpreting the results of mathematical problem-solving. These skills are influenced by several factors, including reading comprehension, learning motivation, teachers' instructional strategies, and the availability of learning resources. Therefore, contextual and problem-based mathematics instruction is necessary to enhance elementary school students' numeracy literacy skills.